2021
DOI: 10.1042/bcj20200511
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatases in cell adhesion

Abstract: Adhesive structures between cells and with the surrounding matrix are essential for the development of multicellular organisms. In addition to providing mechanical integrity, they are key signalling centres providing feedback on the extracellular environment to the cell interior, and vice versa. During development, mitosis and repair, cell adhesions must undergo extensive remodelling. Post-translational modifications of proteins within these complexes serve as switches for activity. Tyrosine phosphorylation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 245 publications
1
20
0
Order By: Relevance
“…RPTPs were discovered in 1988 ( Tonks et al, 1988 ), and have been increasingly studied because they not only participate in cellular signaling through their phosphatase activity, but also by acting as adhesion molecules often independently of their catalytic domains ( Young et al, 2021 ). Amongst these dual-function molecules, type IIA RPTPs arise as important modulators of several cellular processes within the brain, acting as signaling and adhesion molecules.…”
Section: Introductionmentioning
confidence: 99%
“…RPTPs were discovered in 1988 ( Tonks et al, 1988 ), and have been increasingly studied because they not only participate in cellular signaling through their phosphatase activity, but also by acting as adhesion molecules often independently of their catalytic domains ( Young et al, 2021 ). Amongst these dual-function molecules, type IIA RPTPs arise as important modulators of several cellular processes within the brain, acting as signaling and adhesion molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The β 1 -, β 2 -, and β 3 -integrins are best known, and many of the regulatory mechanisms appear similar in the different integrin families. A few protein kinases and phosphatases have been identified to be involved in integrin phosphorylation, but here much additional work is needed [ 27 , 54 ].…”
Section: Site-specific Integrin Phosphorylations Regulate Integrin Activitymentioning
confidence: 99%
“…PTP1B expression has been shown to promote tumorigenesis in breast cancers, and several in vivo studies have shown that PTP1B knockout results in delayed tumour formation [129,133,134]. Inhibition of PTP1B results in decreased cell adhesion by downregulation of claudin-1, FAK, and E-cadherin and induces anoikis [120,135,136]. Recently, many anticancer agents have targeted for breast cancer in vitro and in vivo and have shown to act via inhibition of PTP1B activity.…”
Section: Ptp1b and Breast Cancermentioning
confidence: 99%